Customers' satisfaction towards Islamic banking / Ahmad Haziq Mohd Rashid - Mohd Rashid, Ahmad Haziq (2014)
Islamic Banking has become a substantial and fastest growing industry during the last four decades. lt is essential for Islamic banks to sound their customers' base through retaining existing customers and attracting new customers in order to prevail in Malaysia in such a competitive market. For this purpose, it is required to identify those factors which are directly related to the satisfaction of customers towards Islamic banking. The purposes of this study were to identify those factors which are directly linked with the satisfaction of customers towards Islamic banking operations, rank the determined factors to base of Islamic banking customers' responses and examine the relationship of determining factors with Islamic banking customers' satisfaction. As the result, all analysis that have been done show a positive relationship between independent variables and dependent variables and reject all the H” in the hypothesis.